Potential Role of Adjuvant Lenvatinib in Improving Disease-Free Survival for Patients With High-Risk Hepatitis B Virus-Related Hepatocellular Carcinoma Following Liver Transplantation: A Retrospective, Case Control Study - Han, Bing; Ding, Han; Zhao, Shuai; Zhang, Yichi; Wang, Jian; Zhang, Yue; Gu, Jinyang (Frontiers in Oncology, 2020)
Background and Aim: Although liver transplantation (LT) is one of the most effective treatments for the patients with hepatocellular carcinoma (HCC), the high-risk patients suffer from a high ratio of tumor recurrence after LT. Lenvatinib, as a novel targeted drug, has shown an excellent effect in the treatment of advanced HCC, but there is no study on its effect in preventing HCC recurrence in the patients undergoing transplantation. Therefore, this study was designed to evaluate the role of adjuvant lenvatinib in preventing recurrence of high-risk LT recipients with HBV-related HCC, Methods: We retrospectively analyzed 23 high-risk patients consisting of lenvatinib group (n=14) and control group (n=9) with HBV-related HCC who underwent LT in our center. Disease-free survival (DFS) and HCC recurrence of the two groups were compared. The adverse events (AEs) and drug tolerance of lenvatinib were evaluated. Results: The median DFS in lenvatinib group was 291 (95%CI 204-516) days, significantly longer than 182 (95%CI 56-537) days in control group (P=0.04). Three patients in lenvatinib group (21.4%) and 5 patients in control group (55.6%) had short-term HCC recurrence (P=0.11). All patients in lenvatinib group could tolerate oral lenvatinib for at least 3 cycles except 6 cases (42.9%) of dose reduction and 1 case of interruption (14.3%). Thirteen patients (92.9%) taking lenvatinib experienced AEs. The most common AEs were hypertension (64.3%) and proteinuria (42.9%), and the most serious AEs were Grade 3 for 4 cases (28.5%) according to common terminology criteria for adverse events (CTCAE) version 5.0. Additionally, no influence of lenvatinib on the dosage and blood concentration of FK506 was observed. Conclusions: Adjuvant lenvatinib had a potential benefit on prolonging the DFS and reducing the recurrence of high-risk HBV-related HCC patients following liver transplantation with an acceptable drug safety and patient tolerance.